ISOLASI DAN SELEKSI MIKROBA AMILOLITIK DARI MAKANAN FERMENTASI/RAGI TAPAI GAMBUT DI KALIMANTAN SELATAN - Elidar Naiola (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
Fourteen isolates of microbe which produce amylase were isolated from various fermented foods/ragi tapai at South Kalimantan. Three out of them were produce the higher amylase activities compared to others which shown the clear zone areas after pouring with Iodium solution with relative activities > 3. From the studies on morphological and physiological characterization, it was indicated that one isolate was belong to yeast, it was namely Candida sp (ISO RTG). The amylase activity of Candida sp (ISO RTG) was studied in media containing soluble starch, and result showed that the maximum activity of amylase reach after 3 days, it was 1.85 × 102 U/ml (one unit activity is define as μmol of glucose produce per ml per minute). In medium content rice flour as a carbohydrate sources, the maximum activity was 1.91 × 102 U/ml. The optimum temperature for enzyme reaction was at 40–45° C while optimum pH was at pH 5.0–6.0 and the enzyme was relatively stable under such conditions.